IN VITRO MICROPROPAGATION OF NAUCLEA DIDERRICHII (DE WILD &T. DURAND) MERRILL: EFFECT OF NODES POSITION ON PLANTLETS GROWTH AND ROOTING - Rassimwai Pitekelabou; Atsou Vincent Aidam; Kouami Kokou (European Scientific Journal, ESJ, 2015)
In tissue culture, the reactivity of explants in culture depends on their position on mother –plant or their physiological development level. This study aims to determine the regenerative potentialities of nodes according to their position for suitable in vitro micropropagation of N. diderrichii’s seedlings. Thus the effect of uninodal explants position of Nauclea diderrichii on seedling growth and rooting was studied in vitro. Three types of nodes (apical, middle and basal node) excised from two months old seedlings were tested using Woody Plant Medium (WPM) containing 30 g/L of sucrose and solidified with agar-agar at 8 g/L. The mean number of roots and shoots per plant was scored as well as the shoots and roots length was measured after six weeks of culture. Apical nodes produced seedlings with highest number of roots (6.80 ± 2.44 roots / plant) followed by basal (5.70 ± 2.68 roots / plant) and middle nodes (4.50 ± 2.12 roots / plant). But middle and basal nodes produced the best number of shoots (1.90 ±0.31 shoots / plantlet) than that obtained with apical nodes (1.30 ±0.57 shoots / plantlet). Seedlings obtained from apical nodes expressed efficient growth (4.70 ± 1.70 cm) compared to the middle (2.18 ± 0.97 cm) and basal nodes (2.33 ± 1.08 cm). So, for a rapid in vitro production of N. diderrichii’s seedlings, apical nodes of in vitro plants are more suitable.